Synthesis of Bromo Eugenol Derivatives with Molecular Bromine - Verucha Fauzia Putri; Purwantiningsih Sugita; Budi Arifin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
The bromination of eugenol using molecular bromine (Br2) has been widely reported. However, the outcomes have been inconsistent, and as a result, the specific steps of the bromination process have not been definitively established. This research aims to synthesize various derivatives of bromo eugenol, incorporating bromine atoms either in the alkene group, the aromatic ring, or both. The synthetic approaches employed include: (1) direct bromination of eugenol using 1.2, 2.4, and 3.6 equivalents (equiv) of Br2 in chloroform, (2) bromination of eugenyl benzoate with 2.4 equiv of Br2 in chloroform, and (3) debromination of the 1,2-dibromide functionality in selected bromination products using an excess of zinc in ethanol. The bromination steps of eugenol were then proposed based on the composition of the products obtained. Alkene bromination of eugenol predominated with 1.2 equiv of Br2, followed by aromatic bromination with excess Br2 (2.4 and 3.6 equiv). Aromatic substitution primarily occurred at position 6 (ortho to the hydroxyl group) and subsequently at position 5 (para to the methoxy group). Based on these results, we propose that the bromination of eugenol with Br2 proceeds initially through electrophilic addition to the alkene group, followed by electrophilic substitution on the aromatic ring. Protection of the phenol as a benzoyl ester shifted the regioselectivity of the first aromatic bromination from position 6 to 5. Furthermore, the 1,2-dibromide group has been successfully removed by zinc, resulting in derivatives containing bromine atoms only at the aromatic ring. This is by far the first comprehensive report on the bromination of eugenol with Br2 and the first one reporting the bromination of alkene as the main route of bromination with a nearly equimolar amount of Br2.